Mg-C-O isotopes and elements reveal the origin of dolostone in the Middle Jurassic Buqu Formation - Li, Xi; Shen, An Jiang; Hao, Ruilin (Petroleum Science, 2025)
The origin of dolostone in the Middle Jurassic Buqu Formation of the Plateau Basin has been a subject of prolonged debate. This study combines detailed petrological observations with analyses of Mg-C-O isotopes and elements to constrain the origin of dolostones in the Buqu Formation. Petrography and cathodoluminescence (CL) examination identified three types of matrix dolostones: very finely to finely crystalline dolostone (D1), finely to medium crystalline dolostone (D2), and medium to coarsely crystalline dolostone (D3). The analysis of the diagenesis sequence reveals that D1 originated from the dolomitization of grainstone in the early diagenetic phase, whereas D2 and D3 resulted from the recrystallization of D1 during the later burial phase. The presence of high Na (>100 ppm), low Fe (<1000 ppm), low Mn (<250 ppm), positive Ce anomaly, LREE enrichment, stable δ26Mg (−2.28‰ to −2.04‰), and δ13C (1.02‰–2.95‰) indicates that the early dolomitization fluid was oxidized seawater. As the crystal size increases (D1→D2→D3), the progressively rising Mn content and significantly negative δ18O (−10.72‰ to −7.81‰) suggest that the dolostone has experienced modification and alteration by buried pore water in the later stages. The fluctuations in relative sea level during the sedimentary deposition of the Buqu Formation were reconstructed through the utilization of Na, Sr/Cu, Sr/Ba, Rb/Sr, ∑REE, and δ13C. It was observed that the δ26Mg of dolostone closely mirrored the variations in sea level. The consistent trend of change confirms that sea level fluctuations control the formation and distribution of early dolostone. Frequent sea level rise and fall prompted the limestone deposited on the carbonate platform to be continuously transformed into dolostone, which accumulates over a long period to form large-scale thick dolostone. After the formation entered the burial stage, under the combined action of high Mg/Ca ratio pore water, high temperature, and high pressure, the early dolostone experienced the adjustment of burial dolomitization. This research offers a typical case study on the application of Mg-C-O isotope and elements to determine the origin of dolostone. This will aid in a more comprehensive understanding of the formation process of dolostone in ancient rock records.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Buqu formation; Burial adjustment dolomitization; Mg-C-O isotopes; Origin of dolostone; Plateau basin; Sea level changes

Mineralogy and elemental geochemistry of pyrite coal-balls, Datong Coalfield, Shanxi Province, China: Implications for differentiation mechanism - Hao, Huidi; Huang, Wenhui; Hao, Ruilin; Mu, Nana; Wen, Long; Yu, Chunlan (Ore Geology Reviews, 2023)
The pyrite coal-balls found in No.9 coal of Taiyuan Formation in Dongzhouyao Mine of Datong Coalfield were selected to investigate its mineralogy and elemental geochemistry using optical microscope observation, scanning electron microscopy combined with an energy-dispersive X-ray spectrometer (SEM-EDX), inductively coupled plasma mass spectrometry analysis (ICP-MS), laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS), and electron probe micro-analysis (EPMA). Due to the high content of pyrite, the major-element oxides in the coal-ball samples were mainly Fe2O3, with an average of 62.68 %. LA-ICP-MS results showed that coal-balls were enriched in Tl (CC = 32.79), Pb (CC = 9.22), and Mo (CC = 2.07), while the coals in the same layer were enriched in Ga (CC = 5.31), Tl (CC = 3.66), and Li (CC = 2.27). Affinities to S or Fe and the variation of elemental concentration in the environment during the formation of coal-balls were the primary factor of the elemental differentiation between coals and coal-balls, as well as within coal-balls. The coal-balls formed in four stages in a marine-continental transition environment, with Fe from terrestrial sources and S from marine phases, and its physical origin is basically consistent with that of some Carboniferous-Permian coals in the Datong Coalfield. According to the formation sequence and geochemical characteristics, four periods of pyrite coal-balls evolution have been proposed.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Coal-balls; Datong Coalfield; Formation mechanism; Geochemical characteristics; Mineralogical characteristics

Multi-Phase Dolomitization in the Jurassic Paleo-Oil Reservoir Zone, Qiangtang Basin (SW China): Implications for Reservoir Development - Hao, Ruilin; Pan, Liyin; Mu, Nana; Li, Xi; Fu, Xiaodong; Xiong, Shaoyun; Liu, Siqi; Zheng, Jianfeng; She, Min; Munnecke, Axel (Minerals, 2024)
The age and dolomitization processes in the Paleo-oil reservoir zone, which is composed of massive dolostones found in the Qiangtang Basin (SW China), are still debated. In this research, the Long’eni-Geluguanna Area was selected. Macroscopic information, thin sections, and geochemical methods were used to investigate the dolomitization characteristics and the processes that controlled dolomitization. Five types of replacive dolomites and two types of dolomite cement were observed. Some of the dolomites displayed ghosts of primary sedimentary structures. Saddle dolomites were prevalent, occurring in the interparticle and moldic pores of the limestone which should have been filled at an early diagenetic stage. Ten microfacies types were identified. The foraminifera assemblage provides evidence that the studied interval is of Early Jurassic age. The δ13C values are similar to the contemporaneous seawater signature. The REE+Y patterns of limestones and dolostones exhibit similarities to that of seawater. The mean Na and Sr values are comparable to those of other near-normal seawater dolomites. The δ18O values of all lithologies are markedly depleted. The dolomitization started penecontemporaneously, with deposition. A general sand shoal setting with patch reefs developed. The dolomitizing fluids, near-normal seawater, was probably formed by slight evaporation on top of the shoal. Saddle dolomites in the interparticle and moldic pores might indicate hydrothermal activity, which also caused the recrystallization of some pre-existing dolomites. The recrystallization might have slightly increased the crystal size, demolished the ghost structures, formed saddle dolomites, and altered the REE+Y patterns. The recrystallization extent diminished with increasing distance from the fluids-providing fracture. Furthermore, the existence of protected areas within the sand shoal settings could enhance the vertical and horizontal heterogeneity of dolostone reservoirs.
CRIS-Team Scopus Importer:2024-10-04
Keywords: dolomitization; dolostone; microfacies analysis; Qiangtang basin; sedimentary environment